MRI detection of changes in tissue sodium concentration in brain metastases after stereotactic radiosurgery: a feasibility study - Mohamed, Sherif A.; Adlung, Anne; Ruder, Arne Mathias; Hösl, Michaela; Schad, Lothar R.; Groden, Christoph; Giordano, Frank Anton; Neumaier-Probst, Eva (Journal of neuroimaging, 2021)
BACKGROUND AND PURPOSE To date, treatment response to stereotactic radiosurgery (SRS) in brain metastases (BM) can only be determined by MRI evaluation of contrast-enhancing lesions in a long-time follow-up. Sodium MRI has been a subject of immense interest in imaging research as the measure of tissue sodium concentration (TSC) can give valuable quantitative information on cell viability. We aimed to analyze the longitudinal changes of TSC in BM measured with 23Na MRI before and after SRS for assessment of early local tumor effects. METHODS Seven patients with a total of 12 previously untreated BM underwent SRS with 22 Gy. In addition to a standard MRI protocol including dynamic susceptibility-weighted contrast-enhanced perfusion, a 23Na MRI was performed at three time points: (I) 2 days before, (II) 5 days, and (III) 40 days after SRS. Nine BMs were evaluated. The absolute TSC in the BM, the respective peritumoral edemas, and the normal-appearing corresponding contralateral brain area were assessed and the relative TSC were correlated to the changes in BM longest axial diameters. RESULTS TSC was elevated in nine BM at baseline before SRS with a mean of 73.4 ± 12.3 mM. A further increase in TSC was observed 5 days after SRS in all the nine BM with a mean of 86.9 ± 13 mM. Eight of nine BM showed a mean 60.6 ± 13.3% decrease in the longest axial diameter 40 days after SRS; at this time point, the TSC also had decreased to a mean 65.1 ± 7.9 mM. In contrast, one of the nine BM had a 13.4% increase in the largest axial diameter at time point III. The TSC of this BM showed a further TSC increase of 80.1 mM 40 days after SRS. CONCLUSION Changes in TSC using 23Na MRI shows the possible capability to detect radiobiological changes in BM after SRS.
First published: 22 December 2020
Gesehen am 19.01.2022